The alternating current generator - Sidorfsky, Henry August (My University, 1903)
Introduction: 1. Principles of Alternating Currents. Faraday’s discovery that by moving wires across a magnetic field so as to cut lines of force, a current would be induced, suggested the construction of magneto electric machines, drawn by mechanical power. If a coil of wire be revolved between the poles of a magnetic current a current will be induced in the conductors. In Fig. 1. A simple coil C of wire is revolved between the poles of a magnet N S each end of this coil is connected to a slip ring A-B. Now suppose the coil to be revolving so that the top of the coil is coming toward one, then the current induced in the wires at that moment will be in the direction indicated by the arrow heads. It will leave by the ring A. and will return from the circuit through B. Now when the coil is turned 180? degrees from the position shown, the E.M.F. will be reversed and now it will leave the right B. and return through A. Hence in each complete revolution of the coil the E.M.F rises to a maximum, then falls to 0 and then rises to a maximum in the opposite direction. Then we have a primitive form of the alternator, generating a simple periodical alternating current. In alternating current working, the current is rapidly reversed, rising and falling in a set of pulses, the electrical current is being set oscillating, forwards and backwards, through the line and around the circuit with great rapidity under the influence of a rapidly reversing E.M.F. Now, as seen above, the coil by cutting lines of force of the magnetic field sets up a periodic E.M.F. which changes at every half turn giving rise to alternating currents. On each whole revolution there will be an E.M.F. which rises to a maximum and then dies away giving a curve such as is represented in Fig. 2. The heights of the curve above the horizontal line represent the momentary values of the E.M.F.’s; the depths below in the second half of the curve represent the inverse E.M.F.’s that succeed them. The exact slope of this curve depends upon the arrangement of the iron and the winding of the alternator, and also upon the current that is flowing. Some machines are constructed so that their E.M.F. curve is nearly a sine curve, while in other machines the curves vary and sometimes are very irregular. Each complete operation exhibited by the whole wave above and below the line is called a period, and the number of periods in a second is called the frequency or periodicity of the alternator. The number of revolutions per second times the number of pairs of poles gives the frequency.
Citation: Sidorfsky, Henry August. The alternating current generator. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Alternating Currents; Faraday; Magnetic Fields; Electro-Magnetic Field; Alternators; Theses